Differences in Guttae Ultramorphology in Relation to Visual Function in Fuchs Endothelial Corneal Dystrophy - Weller, Julia; Bennemann, Maximilian; Tourtas, Theofilos; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Cornea, 2024)
PURPOSE: The purpose of this study was to investigate the differences in guttae ultramorphology and their relation to visual function in eyes with Fuchs endothelial corneal dystrophy (FECD). METHODS: Thirty FECD eyes without ocular comorbidities were included. Visual functional parameters (best-corrected visual acuity with high-contrast and low-contrast letters and contrast sensitivity/LogCS) and corneal morphology measured with Scheimpflug tomography (Pentacam) were assessed. The surgically removed Descemet membranes were examined by light and transmission electron microscopy. RESULTS: Preoperative mean best-corrected visual acuity (logarithm of the minimum angle of resolution) was 0.52 ± 0.18, LogCS 0.96 ± 0.21 and central corneal thickness 640 ± 55 μm. All eyes had signs of subclinical corneal edema in Scheimpflug tomography; clinically visible corneal edema was present in 40% of eyes. Histological findings included a posterior fibrillar zone (PFZ) in 10 specimens (33%) and abnormal collagen depositions in Descemet membranes in 14 specimens (47%). Guttae buried within the PFZ were present only in eyes with clinically visible edema (n = 4, 13%). There was no difference in visual function results and tomography parameters between eyes with and without PFZ or between protruding guttae and guttae embedded in a PFZ, respectively. CONCLUSIONS: Guttae morphology and density were not correlated with visual functional parameters. Guttae buried in a PFZ occurred only in eyes with clinically manifest edema, and thereby, they are an ultramorphological sign for advanced FECD. Subclinical edema was present in all eyes and might be more relevant for quality of vision than guttae ultramorphology.
CRIS-Team Scopus Importer:2024-10-11